Low computational complexity PTS scheme for PAPR reduction in OFDM system - WANG Ling-yin; CAO Ye-wen (Tongxin xuebao)
Concerning that the main drawback of conventional PTS was the large computational complexity, a new low computational complexity PTS （LCC-PTS） scheme was proposed. In LCC-PTS, the computation for candidate signals was simplified by making use of the relation between phase weighting sequences, which resulted in reducing computational complexity dramatically. Performance analysis show that, compared with conventional PTS, the proposed LCC-PTS scheme can be implemented with lower computational complexity while at no loss of PAPR（peak-to-average power radio） performance of the system.